Weed Science - A Plea for Thought - Revisited - Zimdahl, Robert L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
Weed scientists are confident of increasing production through agricultural technology, including herbicides, but do not must ask if the moral obligation to feed people is sufficient justification for the benefits and harms achieved. A continuing, rigorous examination of the science$1 (Bs goals that leads to appropriate change is advocated. Weed scientists have a research consensus - a paradigm - Weeds must be controlled. Herbicides are the best control technology. Agriculture's practitoners should discuss the necessity and risks of their technology. Discussion must include scientific evidence and value-laden arguments.s
Keywords: Life sciences; Agriculture; Life Sciences; Agriculture